Influência dos recursos tangíveis e intangíveis no desempenho econômico-financeiro das empresas - Giarola, Eduardo (2017)
The objective of this study was to investigate the relationship and measure the effects of tangibility and intangibility of resources in superior and persistent performance of the companies. Superior performance is synonymous with competitive advantage, that is, obtaining economic results above the average of competitors' results. Superior and persistent performance is synonymous with a sustainable competitive advantage, that is, the need to maintain these results in the long term, with effectiveness of the strategic position in the market. The sample was composed of open capital companies, whose stocks were listed in BCBA (Argentina), BM&FBovespa (Brazil), BVC (Colombia) e BMV (México). The data are secondary and are available in the Economática® database. 863 publicly traded companies was analyzed, with quarterly information from 2004 to 2015. The statistic techniques that were used were analysis of statistic panels with estimates nonvariable effects (EF) and dynamic panel approach using the System Generalized of Moments Method (System GMM). The main contribution of the study was the analysis of the relationship between intangibility and tangibility of resources and the economic and financial performance of companies, incorporating the diagnosis by countries and sectors. We stress the creation of a new indicator of economic performance of companies: "Vaic adapted". There two measures for the company's performance. In the first instance, the companies’ performance was measured by the specific profit of the company (LEE), calculated by the difference between the return on assets (ROA) of the company and the average value of ROA of the sector of the economy of which the company is part of. And the specific profit of the company (LEE) calculated by the difference between the return on equity (ROE) of the company and the average value of ROE of the sector of the economy of which the company is part of. The intangibility of resources was measured by the adapted Q of Tobin and adapted Vaic and the tangibility by the Varbook. As main results, the intangibility and tangibility of resources were factors that contributed to the specific profits of the companies, with variations. The general results were consistent with Resource Based View, confirming that the intangibility and tangibility of resources provided positive and significant in superior and persistent performance of the company. There was significant heterogeneity in the economic performance of enterprises in different countries and sectors of the economy. Highlight the significant results for the intangible variable adapted Vaic. This variable evidenced that intangibility of resources contributed to the superior economic-financial performance of companies in the sample. Increases in the levels of intangibility, measured by the adapted Vaic, would lead to increases in specific profit of the company and, consequently, an above-average return on assets and Net Equity. It was concluded that the main contribution of the thesis was the insertion of a new calculation system and, consequently, the presentation of a new indicator for intangibility and economic-financial performance of companies: "Vaic adapted".